Conformational and thermodynamic properties of parallel intramolecular triple helices containing a DNA, RNA, or 2 '-OMeDNA third strand - Asensio, J; Carr, R; Brown, T; Lane, A (1999)
The thermodynamic stability and solution conformational properties of three intramolecular triple helices based on the sequence AGAAGA-x-TCTTCT-x- TCTTCT (x is a non-nucleotide linker) comprising a DNA duplex and DNA, RNA, or 2'-OMeDNA third strands have been compared. The most stable triple helix contains the 2'-OMe third strand, followed by the triplex containing RNA in the third strand. Comparison of the NMR spectroscopic data for the RNA hybrid triplex with those of the all-DNA triplex shows that the duplex parts of the structure are very similar; the major difference is that the RNA strand is characterized by C3'-endo sugars (except the two terminal residues). In the all-DNA triplex γ has a substantial fraction of the trans rotamer for both of the internal adenine residues (A3 and A4), whereas in the free duplex γ is g + for these residues. In the RNA-containing triplex, only A3 shows the presence of γ(t), and in the 2'-OMe state, both A3 and A4 are γ(g +). In addition, the 2'-OMe triplex shows conformational heterogeneity. Thus, there are sugar-dependent differences in the degree of distortion in the purine strand imposed by the third strand binding. The helical parameters for the underlying duplexes are very similar in all three triplexes. However, the helical parameters for the third strands are different for the DNA versus the RNA and 2'-OMe strands, reflecting their different sugar conformations. The lower degree of distortion of the underlying duplex in the presence of the 2'-OMe third strand is consistent with higher thermodynamic stability of this triplex compared with the greater distortion of the duplex induced by both DNA and RNA third strands.